Electrospun Poly(L-lactide-co-ε-caprolactone) Scaffold Potentiates C2C12 Myoblast Bioactivity and Acts as a Stimulus for Cell Commitment in Skeletal Muscle Myogenesis - Serafina Pacilio; Roberta Costa; Valentina Papa; Maria Teresa Rodia; Carlo Gotti; Giorgia Pagnotta; Giovanna Cenacchi; Maria Letizia Focarete (Bioengineering, 2023)
Tissue engineering combines a scaffold, cells and regulatory signals, reproducing a biomimetic extracellular matrix capable of supporting cell attachment and proliferation. We examined the role of an electrospun scaffold made of a biocompatible polymer during the myogenesis of skeletal muscle (SKM) as an alternative approach to tissue regeneration. The engineered nanostructure was obtained by electrospinning poly(L-lactide-co-ε-caprolactone) (PLCL) in the form of a 3D porous nanofibrous scaffold further coated with collagen. C2C12 were cultured on the PLCL scaffold, and cell morphology and differentiation pathways were thoroughly investigated. The functionalized PLCL scaffold recreated the SKM nanostructure and performed its biological functions, guiding myoblast morphogenesis and promoting cell differentiation until tissue formation. The scaffold enabled cell–cell interactions through the development of cellular adhesions that were fundamental during myoblast fusion and myotube formation. Expression of myogenic regulatory markers and muscle-specific proteins at different stages of myogenesis suggested that the PLCL scaffold enhanced myoblast differentiation within a shorter time frame. The functionalized PLCL scaffold impacts myoblast bioactivity and acts as a stimulus for cell commitment, surpassing traditional 2D cell culture techniques. We developed a screening model for tissue development and a device for tissue restoration.